Gintonin stimulates dendritic growth in striatal neurons by activating Akt and CREB - Lim, Hye Kyung; Kim, Kitaek; Son, Youn Kyoung; Nah, Seung-Yeol; Ahn, Soo Min; Song, Minseok (Frontiers in Molecular Neuroscience, 2022)
Gintonin, a glycolipid protein conjugated with lysophosphatidic acid (LPA), is a newly identified compound extracted from Korean ginseng. LPA receptor isotypes exhibit high affinity for gintonin and mediate intracellular calcium signaling in various animal cell models. In this study, we found that gintonin induced the activation of Akt and cAMP-response element binding protein (CREB) in mouse striatal neurons, and chronic treatment with gintonin potently induced dendritic growth and filopodia formation. Gintonin-induced Akt/CREB activation and dendritic development were significantly impaired by LPA receptor (LPAR1/3) inhibition with Ki16425. Intriguingly, prolonged treatment with gintonin ameliorated the reduction in dendritic formation caused by Shank3 and Slitrk5 deficiency in the striatal neurons. In addition, gintonin and brain-derived neurotrophic factor (BDNF) had a synergistic effect on AKT/CREB activation and dendritic growth at suboptimal concentrations. These findings imply that gintonin-stimulated LPA receptors play a role in dendritic growth in striatal neurons and that they may act synergistically with BDNF, which is known to play a role in dendritogenesis.